EFFECT OF SPRAY WITH CARBOLIZER ON THE PRODUCTION OF INDOLE ALKALOIDS INDUCTION FROM LEAVES Catharanthus roseus L. D.GON CLASS MIXPACIFICA - Ahmed, Ekhlas Meteab; Obaid, Ayad Assi (Diyala Agricultural Sciences Journal, 2017)
The experiment was conducted in the lath house - College of AgricultureUniversity of Diyala during 2015 growth season to explain the effect of spraying with Carbolizer at concentration of 0, 2.5 and 3.5 ml l-1 on the indole alkaloids production. The results showed that spraying plants with Carbolizer at concentration of 2.5 ml l-1 gave highest contents of Vindoline and Catharanthine (251.35 and 528.2 µg ml-1 respectively), while spraying with Carbolizer concentration of 3.5 ml l-1 gave the highest quantity of Vincristine and Vinblastine (162.34 and 734.229 mg ml-1 respectively).